Butter production, processing and handling practices at smallholders level in the central highlands and southwest midlands of Ethiopia - Tola, A.; Tola, Y.B.; Kassa, T.; Grace, Delia; Beyene, F.; Tolemariam, T. (2020)
Cross-sectional study of smallholder butter production, processing and handling practices was conducted in the central highlands and south-western midlands of Ethiopia. Semi-structured questionnaire was pre-tested and used for data collection and 532 respondents were purposively selected and interviewed. Statistical Package for Social Sciences and SAS were used to analyse the data. Results show that, women were entirely responsible for butter production and handling and the product is mainly used for income generation, flavouring of locally made foods and stews and hair dressing in the study areas. Amount of raw milk fermented for butter making at a time (7.16 ± 2.43 litres), fermentation time (3.92 ± 0.71 days), churning time (2.12 ± 0.21 hours), quantity of butter produced (0.49 ± 0.01 kg), butter sold /week (0.49 ± 0.02 kg) and butter used for different purposes (0.28 ± 0.06 kg/week) varied significantly (P< 0.05) between the sites. Local butter preservation methods include ghee making, salting and spicing are major ones. PHL of butter occurs in the study areas due to different reasons. Coping mechanisms to mitigate the loss includes use of umbrella to shield butter from direct sunlight and heat while traveling to and in the local markets, storing butter for overnight in buckets of cold water before transporting butter to local markets. Processing, storage, and packaging materials (clay pots and gourds) used for local butter, handling and preservation practices such as spicing and salting were not optimized. Cost-effective strategies can be applied to optimize the current practices to supply adequate, better quality and safe butter. There is a need of dairy processing technologies and dependable marketing systems in the rural areas. It is also vital to assure the safe production, handling and delivery of local butter by creating awareness to the smallholder butter producers.